The assassination of Mephibosheth: Royal and redactional intrigue in the book of Samuel - Bailey, Jeremiah N (Journal for the study of the Old Testament, 2019)
This article explores the textual variation of the name of the son of Saul referenced in 2 Sam 3-4. While the MT reads Ishbosheth, 4QSama and LXX read Mephibosheth. The vague reading in MT 2 Sam 4:1-2 of the son of Saul' probably indicates that the parent text of the MT once also referenced Mephibosheth. While the variant is widely understood to be a simple accidental scribal insertion, this article argues that it instead reflects the redactional development of Samuel. It does this by (1) considering the implications of 2 Sam 21:1-14 for the rise of the Davidic dynasty and the fall of the Saulides, (2) bringing the question of Samuel's sources and their integration to bear on the textual issue, and (3) considering ways that this reading of Samuel clarifies the story in 2 Sam 3:7-11.